Handbook of Evidence-Based Practices in Autism Spectrum Disorder - Reichow, B.; Doehring, P.; Volkmar, F.R. (2025)
The handbook examines the empirical status of interventions and treatments for individuals with autism spectrum disorder (ASD). It offers an insightful and balanced perspective on topics ranging from the historical underpinnings of autism treatment to the use of psychopharmacology and the implementation of EBPs. The book reviews the conceptualization of evidence-based practices (EBPs) as well as considerations for implementing such practices across settings. In addition, it describes emerging treatments – though they cannot yet be considered evidence-based – that have produced limited but highly promising results. The book also describes treatments and therapies that have been proved ineffective. It explores ways in which EBPs can be applied in inclusive school settings, pedatric settings, in-patient treatment progams, and college-based programs for transition-aged youth. The volume describes outcomes from the development of EBP guidelines at the national level (in Scotland) and, more broadly, in the United States and outlines how such guidelines can be adapted to offer more individualized intervention. Key areas of coverage include: Comprehensive treatment models, including early intensive behavioral intervention, pivotal response treatment, Early Start Denver Model, and Naturalistic Developmental Behavioral Interventions. Focal treatments addressing the core deficits of ASD and its co-occuring conditions. Social skills, communication, and the use of applied behavior analysis (ABA) practices for teaching new skills and decreasing challenging behaviors. Sensory-based interventions, psychopharmacology, cognitive behavior therapy, and parent education programs (e. g., Project ImPACT). The Handbook of Evidence-Based Practices in Autism Spectrum Disorder is an invaluable resource for researchers, professors, and graduate students as well as clinicians, therapists, and all professionals working in the fields of developmental, clinical child, and school psychology, pediatrics, social work, behavior analysis, allied health sciences, public health, child and adolescent psychiatry, early childhood intervention, and general and special education. © Springer Nature Switzerland AG 2025.
Pages: 537
Keywords: ASD; Adaptive and challenging behaviors and autism; Augmentative and assistive technology and ASD; Autism treatment; Behavioral-developmental interventions and ASD; Cognitive-behavioral therapy (CBT) and autism; Communication deficits and autism; Controversial therapies and autism; Early Intensive Behavioral Intervention (EIBI); Early Start Denver Model (ESDM) and ASD; JASPER and autism spectrum disorder treatment; Parent education and support programs and ASD; Pivotal Response Treatment (PRT) and autism; Project ImPACT and autism spectrum disorder; Psychopharmacology and autism; Sensory-based interventions and autism; Sleep and autism spectrum disorder; Social skills training and autism; Socioeconomic status and autism treatments; TEACCH® Autism Program; The SCERTS® Model; community settings; dept.sed; medical